2020
DOI: 10.29037/ajstd.627
|View full text |Cite
|
Sign up to set email alerts
|

Sea Level Rise in Indonesia: The Drivers and the Combined Impacts from Land Subsidence

Abstract: Sea level changes play an important role as an indicator of climate change. However, without climate change, the sea level itself shows strong regional patterns, both in space and time, that could deviate significantly from global averages. The spatial variability of sea level changes in Indonesia can be divided based on its drivers, i.e., climatic and seasonal weather-driven and non-climatic and geological-driven. Seasonally, the sea level in Indonesia is generally high in northwest monsoon and low in southea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
0
15
0
2
Order By: Relevance
“…With limited land area and rich biodiversity, the Indonesian archipelago is experiencing LULCC driven by climate change and anthropogenic drivers. Climate change in this area is projected to lead to increased temperatures, intense rainfall [23], and sea-level rise [24]. Sea-level rise, combined with land subsidence, results in increased flooding, increased storm surges, shoreline erosion, and storm exposure in coastal areas [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…With limited land area and rich biodiversity, the Indonesian archipelago is experiencing LULCC driven by climate change and anthropogenic drivers. Climate change in this area is projected to lead to increased temperatures, intense rainfall [23], and sea-level rise [24]. Sea-level rise, combined with land subsidence, results in increased flooding, increased storm surges, shoreline erosion, and storm exposure in coastal areas [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The coastal area of Java has seasonal sea level variations with monsoon variability. Sea level in Indonesia is generally high during the northwest monsoon and low during the southeast monsoon (Triana and Wahyudi 2020). Triana and Wahyudi (2020) also suggested that sea level anomalies (SLAs) in Indonesia are possibly generated by extreme natural phenomenon events (such as La Niña and El Niño), while Fadlan et al (2017) argued that sea level rise in the tropics is not only caused global warming but also by inter annual variability, such as the El Niño Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD).…”
Section: Introductionmentioning
confidence: 99%
“…Sea level in Indonesia is generally high during the northwest monsoon and low during the southeast monsoon (Triana and Wahyudi 2020). Triana and Wahyudi (2020) also suggested that sea level anomalies (SLAs) in Indonesia are possibly generated by extreme natural phenomenon events (such as La Niña and El Niño), while Fadlan et al (2017) argued that sea level rise in the tropics is not only caused global warming but also by inter annual variability, such as the El Niño Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD). Further, some research states that sea level rise in southern Java continues to increase from year to year by several orders of magnitude, and that the causes of this are likely climate change; interannual phenomena, such as ENSO and IOD; as well as seasonal phenomena, such as monsoons (Fadlan et al 2017;Wirasatriya et al 2017;Triana and Wahyudi 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia memiliki potensi kenaikan muka air laut yang tinggi karena pengaruh iklim, musim, dan tatanan geologi yang unik (Triana & Wahyudi, 2020). Perubahan iklim yang terjadi karena pemanasan global semakin mendorong percepatan kenaikan muka air laut tersebut.…”
Section: Pendahuluanunclassified